2009
DOI: 10.1029/2008gl036350
|View full text |Cite
|
Sign up to set email alerts
|

How declining aerosols and rising greenhouse gases forced rapid warming in Europe since the 1980s

Abstract: [1] Mainland Europe's temperature rise of about 1°C since the 1980s is considerably larger than expected from anthropogenic greenhouse warming. Here we analyse shortwave and longwave surface forcings measured in Switzerland and Northern Germany and relate them to humidity-and temperature increases through the radiation-and energy budget. Shortwave climate forcing from direct aerosol effects is found to be much larger than indirect aerosol cloud forcing, and the total shortwave forcing, that is related to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
112
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 27 publications
18
112
0
2
Order By: Relevance
“…1a). The change in SAT during the recent 16 years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) relative to the early period 1964-1993 ranges from 0.93 to 1.10 °C from four data sets, consistent with previous studies (Ruckstuhl et al 2008;Philipona et al 2009;van Oldenborgh et al 2009). The rapid summer mean warming over Western Europe was also accompanied by changes in temperature extremes.…”
Section: Observed Changes In Summer Mean Temperature and Temperature supporting
confidence: 78%
See 1 more Smart Citation
“…1a). The change in SAT during the recent 16 years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) relative to the early period 1964-1993 ranges from 0.93 to 1.10 °C from four data sets, consistent with previous studies (Ruckstuhl et al 2008;Philipona et al 2009;van Oldenborgh et al 2009). The rapid summer mean warming over Western Europe was also accompanied by changes in temperature extremes.…”
Section: Observed Changes In Summer Mean Temperature and Temperature supporting
confidence: 78%
“…Understanding the nature and drivers of this variability is an essential step in developing robust climate predictions and risk assessments. In the last few decades, Europe has warmed not only faster than the global average, but also faster than expected from anthropogenic greenhouse gas increases (Ruckstuhl et al 2008;Philipona et al 2009;van Oldenborgh et al 2009). With the warming, Europe experienced record-breaking heat waves and extreme temperatures that imposed disastrous impacts on individuals, and society (Stott et al 2004;Fischer and Schär 2010;Barriopedro et al 2011;Christidis et al 2011Christidis et al , 2012Hegerl et al 2011;Rahmstorf and Coumou 2011;Hoerling et al 2012;Schubert et al Abstract Analysis of observations indicates that there was a rapid increase in summer (June-August) mean surface air temperature (SAT) since the mid-1990s over Western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…At least as important are changes in the prescribed SSTs, which, however, may encapsulate changes do to aerosols (see section 3.4). Based on observational data, Philipona et al [2009] arrive at similar conclusions. Looking at model results for BC, Jones et al [2011] also caution that factors other than aerosol induced changes in SSR may be important for the explanation of observed recent surface temperature changes.…”
Section: Aerosol Emissions and Surface Temperaturesupporting
confidence: 64%
“…[5] Changes in SSR may have an impact on surface temperature [Stanhill, 1995;Qian and Giorgi, 2000;Liepert, 2002;Menon et al, 2002;Ramanathan et al, 2005;Wild et al, 2007;Ruckstuhl et al, 2008;Philipona et al, 2009] and the hydrological cycle [Ramanathan et al, 2001;Ohmura and Wild, 2002;Menon, 2004;Liepert et al, 2004;Takemura et al, 2005;Huang et al, 2007;Wild et al, 2008]. The relative importance of SSR changes for surface temperatures in comparison to other factors, like greenhouse gas warming, is currently debated Zhou et al, 2010;Jones et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al (2013) found that among 22 climate models, those thatand inferred that improved air quality has led to a strong increase in JJA SWdn there. The Eshel (2016) result is similar to European studies that have tied aerosol reductions to enhanced SWdn (Philipona et al, 2009;Ruckstuhl et al, 2008). Tosca et al (2017) compared the observed +0.54 ± 0.52 K decade −1 summertime temperature trend in the southeast US to the −0.05 decade −1 satellite retrieved AOD trend.…”
Section: Introductionsupporting
confidence: 68%